Islamic law perspective on the bajo indigenous people's marriage tradition in Adonara village - Muhamad Subhi Apriantoro; Viki Saputra Rogi Makin; Muhamat Nur Maarif (Program Studi Hukum Keluarga Islam, 2023)
Even though the tradition is followed, customary cultural traditions in the execution of marriage procedures are a type of habit that is ingrained and attached to customary norms, social values, and community personality values in social life that have certain sacred values that are permanent and difficult to change or difficult. They have their own methods that they have used from generation to generation. However, when these procedures are considered from the perspective of religious teachings, it raises a number of issues as to whether or not they are in line with these teachings. This paper investigates the traditional Bajo marital practices in light of Islamic law. The methods of observation, interviews, and documentation will all be managed utilizing a qualitative methodology system using procedures in order to acquire accurate and comprehensive data and information that supports and supports this writing. The findings of this study include a number of practices that do not go against Islamic religious principles, such as Masuro/Gau ala '(application), the procedure of enforcing the marriage contract (ijab kabul), and punishing men who enter into Gau Raha'/slayyang marriages (eloping).